Association of imbalanced sex hormone production with excessive procoagulation factor SerpinF2 in preeclampsia. Issue 1 (January 2019) - Shao, Xuan; Wang, Yongqing; Liu, Yanlei; Guo, Xuejiang; Li, Dong; Huo, Ran; Jia, Wentong; Cao, Guangming; Li, Yu-Xia; Liu, Ming; Sha, Jiahao; Zhao, Yangyu; et al.
Abstract : Background: Preeclampsia, a serious pregnancy-associated syndrome, is the leading cause of maternal and perinatal morbidity and mortality. Significant exacerbation of the hypercoagulation status as well as imbalanced steroid hormones have been reported in developed preeclampsia. However, it remains unclear whether the two pathological changes are directly associated. Method and results: Our proteomic analysis revealed a significantly elevated SerpinF2/α2-antiplasmin level in preeclampsia plasma. Measurement of the longitudinally gestational change of plasmin-α2-antiplasmin (PAP) complex, testosterone, estradiol in preeclampsia patients and normal pregnant women demonstrated that the circulating PAP and testosterone levels in the early-onset preeclampsia (E-PE) patients were substantially higher, whereas estradiol concentration was significantly lower than that in normal pregnant controls from early pregnancy throughout gestation. Correlation analysis revealed that circulating PAP is in positive correlation with the concentration of testosterone, and in negative correlation with estradiol in E-PE patients. In E-PE placenta, the productions and activities of 17β-hydroxysteroid dehydrogenases 3 and aromatase, the essential enzymes for testosterone and estradiol synthesis, were compromised. In human renal and trophoblastic cells, testosterone and estradiol could regulate SerpinF2 expression in opposite ways. In addition, obvious fibrin deposition was colocalized with SerpinF2 in intervillous spaces and the area surrounding syncytiotrophoblasts in E-PE placenta. Conclusion: The findings reveal a tight correlation between the imbalanced steroid hormone production and the procoagulation factor in E-PE patients, which provide potential biomarkers to predict preeclampsia, and bring new insight into the pathogenesis of preeclampsia. Abstract : Supplemental Digital Content is available in the text